Free-standing, flexible thermochromic films based on one-dimensional magnetic photonic crystals - Ma, Huiru; Zhu, Mingxing; Luo, Wei; Li, Wei; Fang, Kai; Mou, Fangzhi; Guan, Jianguo (Journal of materials chemistry. C, Materials for optical and electronic devices, 2015)
We have in this paper developed a simple, one-step strategy to fabricate free-standing, flexible thermochromic films at a centimeter scale by the instant free radical polymerization of a sterically stabilized magnetically responsive photonic crystal (MRPC) nonaqueous suspension containing N -isopropyl acrylamide under an external magnetic field ( H ). In the as-prepared thermochromic films, the uniform superparamagnetic polyvinylpyrrolidone-coated Fe 3 O 4 colloidal nanocrystalline cluster (Fe 3 O 4 @PVP CNC) particles exist as a form of one-dimensional (1D) nanochain-like photonic crystal structures parallel oriented along the direction of H in the poly( N -isopropyl acrylamide) (PNIPAM) gel matrix. Since the PNIPAM matrix has a much smaller refractive index than that of the Fe 3 O 4 @PVP CNC particles, and may remarkably change its volume and thus the lattice constants with temperature, the as-prepared thermochromic 1D PC films can display bright iridescent colors which are obviously sensitive to temperature with good reversibility and durability even when the volume fraction of the Fe 3 O 4 @PVP CNC particles is as low as 0.1 vol%. For example, the blue-shift range for the diffraction wavelength can reach up to 140 nm when temperature increases from 10 to 35 °C. Compared to the previously reported 3D photonic crystal films, they also have the significant advantages of a facile, instant one-step preparation process and good mechanical properties. Furthermore, the lattice constants and optical properties can be conveniently tuned by altering H or the level of crosslinking during the polymerization process. Therefore, the as-obtained self-standing thermochromic 1D PC films are believed to have potential practical applications as a new generation of thermochromic polymer matrix composite materials.